UJI TOKSISITAS EKSTRAK ETANOL TERPURIFIKASI BIJI MAHONI (Switenia mahagoni) - Virsa Handayani; Ahmad Najib; Rezki Amriati Syarif; Abdullah Mahmud; La Hamidu; Aktsar Roskiana Ahmad (Faculty of Pharmacy, Universitas Muslim Indonesia, 2019)
Mahoni is a medical plant which have the potential as drug. The aims of this research were to analysis phytochemical content and to test the toxicity of ethanol extract of seed from Mahoni. The Phytochemicals that analyzed were total phenolic, total flavonoid and condensed tannin. Toxicity test was assessed using BSLT method. Extraction was done by maseration method using ethanol as the solvent. In BSLT method, the shrimp larvae were placed in a series of test solution of varied concentration. The value of LC50 were obtained based on calculation of shrimp larvae lethality percentage using probit analysis. LC50 values of ethanol extract were 0,95 ppm.